Reaksi Duka pada Remaja: Pengukuran dan Penelusuran (Jurnal Ilmiah Psikologi MIND SET, 2025)
The death of a parent is one of the most sorrowful life events that can happen in adolescence and can lead to potentially traumatic experiences that may impact the further developmental stages of adolescence. Measuring grief reactions in adolescents is essential, it will help identify their conditions. This study aims to construct the instrument and explore adolescent grief reactions by including cognitive responses, emotional reactions, behavioral responses, and physical sensations of adolescents after the death of their parents. Sixty-six adolescents (12 – 17 years) as participants filled out an online form consisting of 48 items related to their conditions, after experiencing a significant loss. This study applied Confirmatory Factor Analysis (CFA) to test the construct validity. The CFA result showed that the instrument is valid because the output coefficients met the acceptable values of goodness-of-fit indicators. The scale is also reliable, with a coefficient of 0.954. Therefore, it is concluded that this instrument is ready to measure the intensity of adolescent grief reactions. This study showed the intensity of grief reactions of 66 adolescents: Very Weak (3%), Weak (24%), Fairly Strong (38%), Strong (33%), and Very Strong (2%).